Efektifitas Alat Permainan Edukatif pada Anak Usia Dini (4-5 Tahun) - Fitriani, Nini; Marni, Sri; Rapena, Rapena; Amrun Mbera, Astinaningsih; Amir, Fitriany; Nasir, Nasir (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
This study aims to evaluate the effectiveness of educational play tools (APE) in teaching numbers to early childhood students aged 4-5 years. The research employed a quantitative approach with a One-Group Pretest-Posttest design. The sample consisted of 15 students from Group A at TK Adhyaksa XII Kendari. Data were collected through pretests, posttests, observations, and documentation. The results revealed a significant improvement in students' average scores from 57.33 (pretest) to 74.00 (posttest). The t-test showed a significant value (p < 0.05), indicating a positive impact of APE on students' learning outcomes. An N-Gain score of 0.3 categorized the improvement as moderate. These findings highlight that APE is effective in enhancing young children's understanding of numerical concepts, although further development is needed for optimal results.